Experimental and kinetic modeling study on the ignition characteristics of methyl acrylate and vinyl acetate: Effect of CC double bond. (15th April 2022) - Li, Chong; Zhang, Zhenpeng; He, Li; Ye, Mingzhi; Ning, Hongbo; Shang, Yanlei; Shi, Jinchun; Luo, Sheng-Nian
Abstract: The ignition characteristics of methyl acrylate (MA) and vinyl acetate (VA) are investigated in a heated shock tube at 1176–1618 K, 4–16 atm, and equivalence ratios of 0.5–2.0. The ignition delay times of MA and VA decrease with increasing equivalence ratio and decreasing pressure but pressure has a negligible effect on their ignition at low temperatures. Comparison between ignition delay times of MA and VA as well as their corresponding saturated esters indicates that both saturation and position of CC double bond affect the ignition process. To reveal its chemical kinetics on ignition characteristics of esters, the existing kinetic model of MA is updated and VA model is further constructed based on the updated MA model. The new kinetic models can better reproduce ignition delay times under current experimental conditions. Comparisons and kinetic analyses demonstrate that MA is more active than VA and H-addition and unimolecular decomposition reactions are the major channels consuming fuel molecules. The reactivities of MA and VA are lower than their corresponding saturated esters at φ  = 0.5 and 1. With increasing temperature and equivalence ratio, the saturated esters become less active than MA and VA because of low decomposition rate and stable intermediate formations, respectively. Highlights: Ignition delay times of vinyl acetate (VA) are first measured in shock tube. Kinetic models are updated and constructed for methyl acrylate (MA) and VA. Unsaturated methyl ester MA is more reactive than unsaturated acetic ester VA. MA and VA are less reactive than corresponding saturated esters at φ  = 0.5 and 1. Unsaturated esters are more reactive at high temperatures (>1480 K) and φ  = 2.